Using Robotics and Game Design to Enhance Children's Self-Efficacy, STEM Attitudes, and Computational Thinking Skills - Leonard, Jacqueline; Buss, Alan; Gamboa, Ruben; Mitchell, Monica; Fashola, Olatokunbo S.; Hubert, Tarcia; Almughyirah, Sultan (Journal of science education and technology, 2016)
This paper describes the findings of a pilot study that used robotics and game design to develop middle school students' computational thinking strategies. One hundred and twenty-four students engaged in LEGO® EV3 robotics and created games using Scalable Game Design software. The results of the study revealed students' prepost self-efficacy scores on the construct of computer use declined significantly, while the constructs of videogaming and computer gaming remained unchanged. When these constructs were analyzed by type of learning environment, self-efficacy on videogaming increased significantly in the combined robotics/gaming environment compared with the gaming-only context. Student attitudes toward STEM, however, did not change significantly as a result of the study. Finally, children's computational thinking (CT) strategies varied by method of instruction as students who participated in holistic game development (i.e., Project First) had higher CT ratings. This study contributes to the STEM education literature on the use of robotics and game design to influence self-efficacy in technology and CT, while informing the research team about the adaptations needed to ensure project fidelity during the remaining years of the study.